Xuebijing enhances antitumor efficacy of anti-CD19 CAR-T cells - Jingjing Zhu; Jing Zhang; Ping Wang; Xiuying Liu; Jingjing Liu; Yichao Feng; Mary Yue Jiang; Zhiqiao Feng; Xiaoqing Yao; Jianxun Wang (Journal of Traditional Chinese Medical Sciences, 2024)
Objective: To investigate the effects and mechanisms of Xuebijing injection (XBJ) on Chimeric antigen receptor-T (CAR-T) cell function and its therapeutic potential against CAR-T therapy-associated cytokine storms (CRS). Methods: Anti-CD19 CAR-T cells were established based on FMC63 antibodies. Different doses of XBJ (1 and 10 mg/mL) were added to the culture system. Untreated anti-CD19 CAR-T cells served as negative controls. After 48-h co-culture, the effects of XBJ on CAR-T cell function were assessed. Carboxyfluorescein diacetate succinimidyl ester staining was used to assess the effect of XBJ on CAR-T cell proliferation. Flow cytometry, luciferase reporter gene assays, and real time cellular analysis were employed to evaluate the effects of XBJ on CAR-T cell cytotoxicity in vitro. RNA-sequencing was performed to analyze the effects of XBJ on CAR-T cell gene expression. Network pharmacology predicted potential XBJ therapeutic targets for CRS, which were verified in a THP-1 macrophage inflammation model. Results: XBJ enhanced both the proliferation and tumor killing capacities of CAR-T cells. Transcriptome analysis showed that XBJ treatment affects multiple genes and pathways in CAR-T cells, with differential gene enrichment in multiple cell proliferation and growth factor pathways. Potential targets for CRS control by XBJ were predicted using network pharmacology, and the inhibitory effect of XBJ on the expression of relevant genes was verified using a macrophage model. Conclusion: The results of this study indicate that XBJ can enhance the killing effect of CAR-T cells on tumor cells and that the mechanism is related to the regulation of T cell proliferation and activation. Moreover, XBJ inhibited excessive inflammation associated with CAR-T therapy. However, the current findings remain to be further validated through in vivo experiments.